A phase 1 study of everolimus plus docetaxel plus cisplatin as induction chemotherapy for patients with locally and/or regionally advanced head and neck cancer. Issue 10 (13th February 2013) - Fury, Matthew G.; Sherman, Eric; Ho, Alan L.; Xiao, Han; Tsai, Frank; Nwankwo, Oby; Sima, Camelia; Heguy, Adrian; Katabi, Nora; Haque, Sofia; Pfister, David G.
Abstract: BACKGROUND: Activation of the phosphatidylinositol‐3‐kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is common in head and neck cancers, and it has been demonstrated that inhibition of mTOR complex 1 sensitizes cell lines to platinum and taxane chemotherapy. The authors conducted a phase 1 study to evaluate the addition of oral everolimus to cisplatin and docetaxel as induction chemotherapy for head and neck cancer. METHODS: In this single‐institution phase 1 study, 3 doses of daily everolimus were explored: 5 mg daily, 7.5 mg daily (administered as 5 mg daily alternating with 10 mg daily), and 10 mg daily of each 21‐day cycle. Cisplatin and docetaxel doses were fixed (both were 75 mg/m 2 on day 1 of 21‐day cycle) at each dose level with pegfilgrastim support. A standard 3 + 3 dose‐escalation plan was used. After induction, patients were removed from protocol. RESULTS: Eighteen patients were enrolled (15 men, 3 women), and their median Karnofsky performance status was 90. The most common toxicities were hyperglycemia, low hemoglobin, fatigue, and thrombocytopenia. Dose‐limiting toxicities (DLTs) were neutropenic fever (1 event at dose level 2, 2 events at dose level 3), and all patients recovered fully from these DLTs. The maximum tolerated dose was exceeded at dose level 3. The progression‐free survival rate at 1 year was 87.5% (95% confidence interval, 56.8%‐96.7%); and, at 2 years, it was 76.6% (95% confidence interval, 41.2%‐92.3%). Activating PI3K catalytic subunit α ( PIK3CA ) gene mutations were identified in 2 human papillomavirus‐associated oropharyngeal cancers. CONCLUSIONS: The phase 2 recommended dose was 7.5 mg daily for everolimus plus cisplatin and docetaxel (both at 75 mg/m 2 on day 1 of a 21‐day cycle) given with pegfilgrastim support. Cancer 2013. © 2013 American Cancer Society. Abstract : This phase 1 study establishes the safety and tolerability of everolimus added to docetaxel/taxotere and cisplatin as induction chemotherapy for head and neck cancer. Everolimus dose levels that are known to be therapeutic are achieved.